2021
DOI: 10.3390/biom11020131
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Alignment of Bone Matrix Microstructure Associated with Disorganized Osteoblast Arrangement in Malignant Melanoma Metastasis

Abstract: Malignant melanoma favors spreading to bone, resulting in a weakened bone with a high fracture risk. Here, we revealed the disorganized alignment of apatite crystals in the bone matrix associated with the homing of cancer cells by developing an artificially controlled ex vivo melanoma bone metastasis model. The ex vivo metastasis model reflects the progressive melanoma cell activation in vivo, resulting in decreased bone mineral density and expression of MMP1-positive cells. Moreover, less organized intercellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The results showed that the apatite orientation of femurs loaded with uniaxial forces was significantly higher than that of the unloaded femurs. We previously reported that the arrangement of the collagen/apatite microstructure was determined by controlling the artificial loading to the bone [17,34,35]. The findings of the present study are consistent with the changes in apatite orientation observed in these in vivo studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that the apatite orientation of femurs loaded with uniaxial forces was significantly higher than that of the unloaded femurs. We previously reported that the arrangement of the collagen/apatite microstructure was determined by controlling the artificial loading to the bone [17,34,35]. The findings of the present study are consistent with the changes in apatite orientation observed in these in vivo studies.…”
Section: Discussionsupporting
confidence: 92%
“…An Ex Vivo Bone Culture Model E16.5 mice (ICR; Japan SLC, Shizuoka, Japan) were anesthetized, and femurs were removed under a light microscope. Referring to previously reported ex vivo bone culture models [34,35], embryonic femurs were cultured in 96-well plates (IWAKI, Tokyo, Japan) and commercially pure (CP) titanium specimens (weights: 0.5 or 1.0 g) for 7 days at 37 • C in 5% CO 2 . The bone was fractured by a 1.5 g load.…”
mentioning
confidence: 99%
“…Changes in bone's ECM composition and organization are characteristic for bone pathologies like osteoporosis, osteogenesis imperfecta, and bone metastasis (Bala and Seeman, 2015;Bishop, 2016;Karunaratne et al, 2016;Matsugaki et al, 2021). Therefore, in vitro models that aim at studying changes in bone ECM under the influence of treatments would benefit from improved control over organic matrix formation and subsequent mineralization (Hadida and Marchat, 2020;de Wildt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering strategies are nowadays increasingly applied for the creation of in vitro models of healthy or pathological bone, aiming at improving preclinical treatment development while addressing the principle of reduction, refinement, and replacement of animal experiments (3Rs) (Balls et al, 1995; Caddeo et al, 2017; Holmes et al, 2009; Owen and Reilly, 2018). Changes in bone’s ECM composition and organization are characteristic for bone pathologies like osteoporosis, osteogenesis imperfecta, and bone metastasis (Bala and Seeman, 2015; Bishop, 2016; Karunaratne et al, 2016; Matsugaki et al, 2021). Therefore, in vitro models that aim at studying changes in bone ECM under the influence of treatments would benefit from improved control over organic matrix formation and subsequent mineralization (Hadida and Marchat, 2020; de Wildt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that these inflammatory cytokines function by promoting RANKL production, reducing OPG production, and/or up-regulating RANK on osteoclast precursors, indirectly affecting osteoclastogenesis [ 4 , 10 , 11 ]. Meanwhile, these inflammatory cytokines inhibit osteoblast proliferation [ 12 , 13 ] and disrupt unidirectional osteoblast alignment [ 14 , 15 ], resulting in improper bone regeneration. Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid.…”
Section: Introductionmentioning
confidence: 99%